Spatial Reasoning of Students With Mathematical Learning Difficulties - Amalia, Alfin Khoiro; Amir, Mohammad Faizal (Jurnal Pendidikan Matematika IKIP Veteran Semarang, 2024)
Spatial reasoning is essential for solving two or three-dimensional oriented problems. Meanwhile, primary school students often experience mathematical learning difficulties (MLD) using spatial reasoning. The research analyzes the spatial reasoning of primary school students who experience MLD. The research method is qualitative, with the research subject being fifth-grade students at one of the primary schools in Sidoarjo. The research instruments used spatial reasoning tests and interview guidelines. The results stated differences in spatial reasoning in students' MLD types. Students who experience visual spatial type MLD have lower spatial reasoning skills because they cannot solve spatial orientation, mental rotation, and spatial visualization problems. Meanwhile, students who experience memory-type MLD have moderate spatial reasoning because they can solve spatial orientation and spatial visualization problems but cannot solve mental rotation problems. The researcher suggested that the subsequent research should intervene in the spatial reasoning of students who experience MLD.